Effects of laparoscopy on the cardiorespiratory system of brown brocket deer (Mazama gouazoubira) anesthetized with ketamine/ xylazine/ midazolam combination and isoflurane - Munerato,Marina Salles (2008)
Laparoscopy is not widely used as a tool to perform assisted reproduction techniques in South American cervids; thus, scarce information in literature is available regarding its effects and appropriate anesthetic protocols to perform it. This study evaluated the effect of laparoscopy on heart rate (HR), respiration rate (RR), saturation of oxyhemoglobin (SpO2) and rectal temperature (RT) of six female brown brocket deer (Mazama gouazoubira) anesthetized with ketamine (5mg/kg), xylazine (0.3mg/kg), midazolam (0.5mg/kg) combination i.v. and isoflurane. Twelve laparoscopies were performed and each animal was used twice with a 40-day interval. After anesthetized, the animals were placed in dorsal recumbency to perform laparoscopy procedure using abdominal CO2 insufflations (14.2 ± 2.39mmHg; M ± SE). The main events of the laparoscopy procedure were divided into three periods: animal without (P1) and with abdominal insufflation (P2) and abdominal insufflation with the hips raised at 45º (P3). As a control, the animals were anesthetized again 40 days after the last laparoscopy, and were maintained in a dorsal recumbency for the same average duration of the previous anesthesia and no laparoscopy procedure was conducted. The period of anesthesia for the controls was also divided into P1, P2, and P3 considering the average duration of these periods in previous laparoscopies performed. Data were analyzed through the (ANOVA) variance analysis followed by Tukey test and values at P<0.05 were considered significant. No significant differences were observed in the parameters evaluated at P1, P2 and P3 between the animals submitted to laparoscopy and control. However, the RR mean between P1 (38.8 ± 4.42) and P3 (32.7 ± 4.81); and the RT mean between the P1 (38.2ºC ± 0.17), P2 (37.6ºC ± 0.19) and P3 (37.0ºC ± 0.21) varied significantly, independent of the laparoscopy. These data indicated that laparoscopy didn't cause any significant alterations in the cardiorespiratory parameters evaluated, even though the anesthetic protocol used can cause a reduction in the RT contributing to development of hypothermia during anesthesia.